Scientific breakthroughs, innovation clusters and stochastic growth cycles - Manfred Stadler (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
We develop a dynamic stochastic general-equilibrium model of science, education and innovation to explain the simultaneous emergence of innovation clusters and stochastic growth cycles. Firms devote human-capital resources to research activities in order to invent higher quality products. The technological requirements in climbing up the quality ladders increase over time but this hampering effect is compensated for by an improving qualification of researchers allowing for a sustainable process of innovation and scale-invariant growth. Jumps in human capital, triggered by scientific breakthroughs, induce innovation clusters across industries and generate long-run growth cycles.
urn:nbn:de:bsz:21-opus-70199
Keywords: C61; E32; O33; 330; Science; Education; Innovation clusters; Stochastic growth cycles